2013
DOI: 10.3389/fphys.2013.00032
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Previa and Pre-Eclampsia: Analyses of 1645 Cases at Medani Maternity Hospital, Sudan

Abstract: A retrospective case-control study was conducted to investigate the risk factors for pre-eclampsia – including the protective effect of placenta previa – at Medani Maternity Hospital, Sudan. Medical files of the patients during the period 2003–2010 were reviewed for age, parity, education level, prenatal care, placenta previa, and hemoglobin level. Women with pre-eclampsia were the cases, and women with normal pregnancy were the controls. There were 54,339 singleton deliveries and 1765 women with pre-eclampsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 26 publications
1
43
0
1
Order By: Relevance
“…Pre‐eclampsia/eclampsia is the leading cause of obstetric complications and maternal mortality in Sudan [9–11]. Consequently, the aim of the present study was to evaluate the incidence of, and predictors for, persistent hypertension in patients with pre‐eclampsia [12–14].…”
Section: Introductionmentioning
confidence: 98%
“…Pre‐eclampsia/eclampsia is the leading cause of obstetric complications and maternal mortality in Sudan [9–11]. Consequently, the aim of the present study was to evaluate the incidence of, and predictors for, persistent hypertension in patients with pre‐eclampsia [12–14].…”
Section: Introductionmentioning
confidence: 98%
“…Preeclampsia is a common medical disorder affecting about 2–7% of pregnant women worldwide [1, 2] and can lead to unfavorable pregnancy outcomes such as increased maternal as well as perinatal morbidity and morbidity [3]. The etiology of preeclampsia remains ambiguous, albeit, reports that implicated placental defects and oxidative stress early during pregnancy in affected pregnancies [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…calcium and zinc supplement [18]. In Sudan, preeclampsia/eclampsia is a major cause of maternal and perinatal morbidity and mortality [1, 19, 20]. We have previously shown that preeclampsia is associated with oxidative stress [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is also more common in nulliparous women, who have not had a previous pregnancy to enable adaptive uterine musculature and vascular responses to occur. It is less common in some groups where high levels of calcium intake is common [12], and in smokers [13] (who also are known to have smaller babies [13]), and there is evidence to suggest that the disease is also less common in women with placenta praevia where there is increased vascularity to the uterus and placenta [14].…”
Section: Risk Factorsmentioning
confidence: 99%